Oral care interventions for the prevention and management of anticancer therapy–induced oral mucositis: A systematic review - Zahra Farivar; Hamid Salehiniya; Leili Alizadeh (Oral Oncology Reports)
Background: Oral mucositis (OM) is a common and debilitating complication of cancer treatments, particularly chemotherapy and radiotherapy. It significantly impacts patients’ quality of life, increases healthcare costs, and can interrupt or delay cancer therapy. This systematic review aimed to evaluate the effectiveness of various oral care interventions in the prevention and management of OM in patients undergoing anticancer treatments. Methods: A systematic literature search was conducted in PubMed, Web of Science, and Scopus databases, adhering to PRISMA guidelines. Eligible studies included clinical trials and cohort studies published between January 2000 and June 2025. The quality of included studies was assessed using the Joanna Briggs Institute (JBI) critical appraisal tools. Results: Out of 2542 records screened, 48 studies met the inclusion criteria. Among these, 16 studies evaluated professional oral health care (POHC), 16 assessed chlorhexidine rinses, 6 focused on patient education, 6 examined sodium bicarbonate rinses, and 4 studied saline rinses. POHC and patient education consistently demonstrated beneficial effects, with over 75 % of studies in these categories reporting significant reductions in OM incidence and severity. Chlorhexidine and saline rinses showed mixed or limited results: only 38 % of chlorhexidine studies and 25 % of saline studies reported a measurable benefit. Risk of bias was rated as low to moderate in most studies, with 14 studies rated as high quality. Conclusion: This review highlights the effectiveness of structured oral care interventions particularly POHC and patient education in mitigating OM among cancer patients. These findings support the integration of evidence-based oral care protocols into routine oncology practice and emphasize the need for standardized clinical guidelines to enhance patient outcomes and quality of life.